Incidence and origin of meiotic whole and segmental chromosomal aneuploidies detected by karyomapping - Kubicek, David; Hornak, Miroslav; Horak, Jakub; Navratil, Rostislav; Tauwinklova, Gabriela; Rubes, Jiri; Vesela, Katerina (Reproductive biomedicine online, 2019)
RESEARCH QUESTION: What is the incidence and origin of meiotic whole and segmental aneuploidies detected by karyomapping at a blastocyst stage in human-derived IVF embryos? What is the distribution of various types of errors, including rare chromosomal abnormalities? DESIGN: The incidence of chromosomal aneuploidies was assessed in 967 trophectoderm biopsies from 180 couples who underwent 215 cycles of IVF with preimplantation genetic testing for monogenetic disease with a known causal mutation with a mean maternal age of 32.7 years. DNA from both parents and a reference sample was genotyped together with the analysed trophectoderm samples by karyomapping (single-nucleotide-polymorphism-based array). RESULTS: Chromosomal abnormalities were detected in 31% of the analysed samples. At least one whole chromosomal aneuploidy was detected in 27.1% of the trophectoderm biopsies, whereas a segmental aneuploidy was detected in 5.1% of the trophectoderm biopsies. Our results reveal that segmental aneuploidies predominantly affect paternally derived chromosomes (70.4%; P < 0.01) compared with whole chromosomal aneuploidies that more frequently affect maternally derived chromosomes (90.1%; P < 0.0001). Also, the frequency of meiosis I (MI) and meiosis II (MII) errors was established in meiotic trisomies; MI errors were observed to be more frequent (n = 102/147 [69.4%]) than MII errors (n = 45/147 [30.6%]). CONCLUSIONS: Karyomapping is a robust method that is suitable for preimplantation genetic testing for monogenetic disease and for detecting meiotic aneuploidies, including meiotic segmental aneuploidies, and provides complex information about their parental origin. Our results revealed that segmental aneuploidy more frequently affects paternal chromosomes compared with whole chromosomal aneuploidy in human IVF embryos at the blastocyst stage.
Keywords: Chromosome Disorders; Genetic Testing; Uniparental disomy; PGT–M; karyotypizace; Preimplantation Diagnosis; genetické testování; chromozomální poruchy; chromozomální aberace; Pregnancy; Segmental aneuploidy; těhotenství; Karyotyping; Adult; dospělí; Meiosis; incidence; preimplantační diagnóza; Fertilization in Vitro; fertilizace in vitro; Chromosome Aberrations; meióza; Karyomapping; aneuploidie; lidé; ženské pohlaví; Aneuploidy; Humans; Female; Incidence; Meiotic errors; PGT–A